THE MIDDLE-CLASS CULTIVATE THEIR CHILDREN'S LEARNING THROUGH A BOURDIEU’S CAPITAL THEORY LENS: Received: 3rd January 2025, Revised: 20th March 2025, 2nd April 2025, Accepted: 17th September 2025, Date of Publication: 10th November 2025 - Ru-Fen Luo (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The impact of parental class systems influences children’s roles and responses in school. Social class, encompassing education, occupation, income, or work, equips parents with unequal resources and opportunities for educational engagement. Parents from higher socioeconomic backgrounds are often able to provide their children with more educational resources. Middle class families occupy a unique position in the spectrum of social class. They often have access to more resources than lower-income families but might not possess the extensive privileges of upper-class families. Middle class parents tend to engage actively in their children’s education, leveraging their resources and knowledge to foster academic success. Parental involvement—or the lack thereof—in education can significantly affect children’s school performance. These disparities undoubtedly play a crucial role in shaping children’s outcomes. As an English teacher and having observed the middle class nurturing numerous learning resources for their children, the research was initiated. The study aims to explore the actual circumstances of how middle class families cultivate learning for their children through the lens of Bourdieu’s capital theory. This theoretical framework, which includes economic, cultural, and social capital, provides a comprehensive approach to understanding the multifaceted ways middle class parents support their children’s education. Based on the research purpose, the ethnographic approach in qualitative research was adopted. Long-term participant observation, informal interviews, and teaching diaries were conducted as research methods. Findings organized that the middle class families strategically combined and adapted their economic, cultural, and social capital to provide a supportive educational environment for their children. The middle class understands the inherent limitations of their cultural capital and skillfully enhances it by accessing external resources. This highlights their nuanced and deliberate approach to using the assets they have. The implications suggest an increased awareness of how the middle class function and strategically leverage their economic, cultural, and social capital to provides assistance and resources to help their children succeed in education.